Pedagogical, Lecturing and Charitable Activities of Ladislav Brtnický, a Classical Philologist (1858-1936) - Koucká, Ivana (Historica Olomucensia, 2012)
The article is devoted to a classical philologist and secondary school teacher Ladislav Brtnický (1858-1936). The focus lies on the analysis of his pedagogical, lecturing and charitable activities, particularly in Hradec Králové. The personal fonds of Ladislav Brtnický housed at the Masaryk Institute and Archive of the Academy of Sciences of the Czech Republic has served as a basic source together with the fonds "Gymnasium J. K. Tyla Hradec Králové NAD: 240" and "Dívčí gymnásium Hradec Králové NAD: 230" housed at the State Regional Archives in Zámrsk, State District Archives in Hradec Králové.Ladislav Brtnický's pedagogical work at classical gymnasium in Hradec Králové consisted of giving classes not only of Latin and Greek but also Czech, German and Philosophical propedeutic. Although he tended more to the research work than teaching, he sought to make the classes more enjoyable by talking about antique writers, showing pictures and narrating his experiences from his trips to Italy and Greece. The end of his teaching career at the girls gymnasium in Hradec Králové belongs to the lesser known periods of his life.After his retirement from teaching L. Brtnický made a series of lectures for various associations and clubs in Hradec Králové and close surroundings. Their topics were related to his scholarly interests and former teaching. His very strong social feeling and sympatization with the woman question lead him and his wife Anna to take part in a wide range of charitable activities. Finally they gave up their house at Eliščino nábřeží (Eliška quay) to install boarding house "Božena Němcová" there, first for girl students of a lyceum, than for girl students of a reformed gymnasium.The final part of the article deals with the issue of non-realised scholarship funds established by L. Brtnický to promote classical studies in his country.